1999
DOI: 10.1161/01.res.85.11.1009
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of Na + /Ca 2+ Exchanger Expression and Function in an Arrhythmogenic Rabbit Model of Heart Failure

Abstract: Abstract-Three-dimensional cardiac mapping in rabbits with nonischemic cardiomyopathy has shown that ventricular arrhythmias initiate by a nonreentrant mechanism that may be due to triggered activity from delayed afterdepolarizations. Delayed afterdepolarizations are thought to be due to spontaneous release of Ca 2ϩ from the sarcoplasmic reticulum (SR) and consequent activation of an inward Na ϩ /Ca 2ϩ exchange (NaCaX) current. The goal of this study was to determine whether there is enhanced NaCaX gene expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

18
323
2

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 359 publications
(344 citation statements)
references
References 56 publications
(64 reference statements)
18
323
2
Order By: Relevance
“…2,3 However, others have suggested that DADs and EADs share a common mechanism that may be NCX dependent. 4 To date, the role of chronically altered NCX expression in the generation of arrhythmia has been limited to models with increased NCX expression 5 and to animal models of heart failure or hypertrophy 1,[6][7][8][9][10] in which NCX is known to be overexpressed. Yet, in heart failure, a multitude of proarrhythmic alterations other than the upregulation of NCX has been identified, 11 most importantly a reduction of K + currents 12,13 which promote a prolongation of AP duration and the occurrence of arrhythmia.…”
mentioning
confidence: 99%
“…2,3 However, others have suggested that DADs and EADs share a common mechanism that may be NCX dependent. 4 To date, the role of chronically altered NCX expression in the generation of arrhythmia has been limited to models with increased NCX expression 5 and to animal models of heart failure or hypertrophy 1,[6][7][8][9][10] in which NCX is known to be overexpressed. Yet, in heart failure, a multitude of proarrhythmic alterations other than the upregulation of NCX has been identified, 11 most importantly a reduction of K + currents 12,13 which promote a prolongation of AP duration and the occurrence of arrhythmia.…”
mentioning
confidence: 99%
“…Specifically, HF cardiac myocytes exhibit depressed and prolonged Ca 2ϩ transients. 1 These changes can be explained by reductions in sarcoplasmic reticulum (SR) Ca 2ϩ -ATPase 2 and increased Na/Ca exchange (NCX) [3][4][5][6] function.…”
mentioning
confidence: 99%
“…Relaxation is accomplished by resequestering of calcium to the sarcoplasmic reticulum by sarcoendoplasmic reticular Ca 2ϩ -ATPase2 (SERCA2) and extrusion of calcium from the cell by NCX1 and plasma membrane Ca 2ϩ -ATPase (PMCA). Abnormal calcium handling caused by altered expression levels or protein activities of NCX1 and SERCA2, or by mutations in ryanodine receptors, have been associated with cardiac diseases, such as heart failure and arrhythmia, and with sudden death in humans and animal models (1)(2)(3)(4)(5)(6). In addition, genetic studies in the zebrafish demonstrate that L-type calcium channels and the sodium pump (a modulator of NCX activity) are indispensable for embryonic cardiac function (7,8).…”
mentioning
confidence: 99%
“…NCX1 is highly expressed in the heart and is considered to be the primary mechanism for calcium extrusion in cardiomyocytes. In fact, elevated NCX1 activity has been noted in patients with heart failure and is associated with arrhythmia in patients and animal models (1,2). The embryonic role of NCX1, however, is not well understood.…”
mentioning
confidence: 99%